1996
DOI: 10.1002/bjs.1800830615
|View full text |Cite
|
Sign up to set email alerts
|

Use of glyceryl trinitrate ointment in the treatment of anal fissure

Abstract: Anal fissure is often treated surgically by sphincterotomy. There is growing concern over the effects of this procedure on continence. Nitric oxide donors such as glyceryl trinitrate are thought to cause a reversible 'chemical sphincterotomy', capable of healing the fissure. Twenty-one consecutive patients with chronic anal fissure (13 women, mean age 36 years) were treated for 4-6 weeks with 0.2 per cent glyceryl trinitrate ointment applied to the fissure twice daily. Maximum anal resting pressure (MARP) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(40 citation statements)
references
References 10 publications
3
36
0
1
Order By: Relevance
“…This age group seems to have higher predilection for development of chronic fissure in ano. This in accordance with study conducted by Christie [7] and Richard [6] where mean age was 35,39,39,44 and 34.7 years respectively. But mean age was 44 and 55 years in study conducted by Palazzo and Schouten [8] respectively.…”
Section: Age Groupssupporting
confidence: 92%
“…This age group seems to have higher predilection for development of chronic fissure in ano. This in accordance with study conducted by Christie [7] and Richard [6] where mean age was 35,39,39,44 and 34.7 years respectively. But mean age was 44 and 55 years in study conducted by Palazzo and Schouten [8] respectively.…”
Section: Age Groupssupporting
confidence: 92%
“…But in the study conducted by Lock & Thombson et al (1977) [3] the posterior fissure were in 75 % of cases, anterior and lateral in 14 % and 3 % respectively. They have found the incidence of sentinel piles to be 38 % .But in the study conducted by Lund [4] the posterior anal fissure was found in 76 % of patients and anterior fissure in 24 % of patients. The proportion of anterior anal fissures is much higher in female patients being 21 % compared with only 9 % in male population [Lock & Thombson et al (1977) [3].…”
Section: Discussionmentioning
confidence: 92%
“…Results of the present were similar to study conducted Lund et al where 18 out of 21 patients were asymptomatic after second week of treatment and Mann et al where 15 out of 16 patients were asymptomatic after four weeks. 6,7 Lund and Scholefield conducted a randomized, prospective, double-blinded, placebo controlled trial of GTN ointment and found that there is marked pain relief after using GTN ointment in comparison to placebo. 8 After six weeks healing was seen in 28 patients out of 50 patients in lignocaine group and 44 patients out of 50 patients in combination group.…”
Section: Discussionmentioning
confidence: 99%